+0  
 
0
144
1
avatar+166 

GIven the system of equations, 

xy= 6 - 2x - 3y
yz= 6 - 4y - 2z
xz= 30 - 4x - 3z

find the positive solution for x

 Jul 5, 2018
 #1
avatar
+1

xy= 6 - 2x - 3y................(1) 

 yz= 6 - 4y - 2z...............(2)                                                                                                                                     
xz= 30 - 4x - 3z..............(3)
From (3) above:
z = (30 - 4 x)/(x + 3)
Sub z into (2) above
y(30 - 4 x)/(x + 3)= 6 - 4y - 2[(30 - 4 x)/(x + 3)]...........(4)
xy= 6 - 2x - 3y..............(1), solve for x, y in (1) and (4)
x = - 9 and y = -4, or:
x = 3  and y = 0
Sub x values into (3) above:
z = 3 and z = -11  

 Jul 5, 2018

31 Online Users

avatar
avatar